Use of Crude Glycerol for Glycerolysis of Free Fatty Acids in Crude Palm Oil - Nanda Suriaini (Universitas Indonesia, 2021)
The glycerolysis of crude palm oil (CPO) using potassium hydroxide was studied. This work aimed to evaluate free fatty acid (FFA) conversion in CPO through glycerolysis using crude glycerol. The effect of molar ratios of FFA to crude glycerol, reaction temperature, stirring speed, and catalyst loading was investigated. The best conditions for the highest FFA conversion of 95.45% were found: 1:4 of FFA to crude glycerol molar ratio, 75°C of reaction temperature, 250 rpm stirring speed, and 0.75% (w/w of oil) of catalyst loading. These conditions have decreased the FFA of CPO from 6.15% to 0.28% in 90 minutes. A kinetic model of the second-order reaction rate was used to quantify the influence of process parameters. It can be concluded that the crude glycerol as a side product of transesterification can be utilized in glycerolysis to lower the cost of biodiesel production.